Aberrant O-glycosylation and anti-glycan antibodies in an autoimmune disease IgA nephropathy and breast adenocarcinoma - Stuchlová Horynová, Milada; Raška, Milan; Clausen, Henrik; Novak, Jan (Cellular and molecular life sciences, 2013)
Glycosylation abnormalities have been observed in autoimmune diseases and cancer. Here, we compare mechanisms of aberrant O-glycosylation, i.e., formation of Tn and sialyl-Tn structures, on MUC1 in breast cancer, and on IgA1 in an autoimmune disease, IgA nephropathy. The pathways of aberrant O-glycosylation, although different for MUC1 and IgA1, include dysregulation in glycosyltransferase expression, stability, and/or intracellular localization. Moreover, these aberrant glycoproteins are recognized by antibodies, although with different consequences. In breast cancer, elevated levels of antibodies recognizing aberrant MUC1 are associated with better outcome, whereas in IgA nephropathy, the antibodies recognizing aberrant IgA1 are part of the pathogenetic process.
Keywords: protilátky; sacharidové sekvence; Mucin-1; molekulární sekvence - údaje; Amino Acid Sequence; nádory prsu; IgA nefropatie; polysacharidy; Breast; Antibodies; Animals; lidé; ženské pohlaví; adenokarcinom; Breast Neoplasms; Humans; zvířata; sekvence aminokyselin; imunoglobulin A; mucin 1; Carbohydrate Sequence; Molecular Sequence Data; Polysaccharides; glykosylace; prsy; Adenocarcinoma; Female; Immunoglobulin A; Glycosylation; Glomerulonephritis, IGA